Second annual meeting 2009 of presidents of Superior Courts of Justice. Arequipa declaration - Villa Stein, Javier (2020)
Presents the declaration of the Presidents of the 29 Superior Courts of Justice of the country that they sign, meeting in the historic city of Arequipa, the cradle of legality, under the leadership of our President of the Judicial Power and of the Supreme Court of Justice of the Republic, Dr. Javier Villa Stein, after two intense days of work, unanimously signed the aforementioned statement